Consumers’ willingness to pay for labelled and certified moringa products in Ogun State, Nigeria (2015)
Major resources are being committed to moringa products innovation and value added production, yet considerable uncertainties still exist regarding public perception of moringa products in terms of labelling and certification. Consequently, understanding consumers’ behaviour will be important if the impact of moringa products on nutrition is to be realized. This study therefore assessed consumers’ perceptions and attitude towards labelled and certified moringa products (tea, spice and oil) and also identified factors influencing their willingness to pay for these products in Ogun State Nigeria. A multistage sampling technique was employed to elicit information from 150 randomly selected respondents within Abeokuta South and Abeokuta North Local Government Areas of Ogun State. Contingent valuation method was used to obtain premiums that consumers are willing to pay for labelled moringa products. Descriptive statistics and the logit regression model were used to analyse the data. Overall, attitude towards moringa products, attitude towards labelling and certification; current purchasing and consumption patterns significantly affected the respondents’ willingness to pay a premium for the labelled and certified moringa products.